Mineralogical Prospecting and Characterization of Auriferous Placers in the Elogo Region: Insights into Primary Gold Deposit Exploration Strategies - Watha-Ndoudy, Noël; Okoumel, Prince Espoire Wamene; Miyouna, Timothée; Mpika , Renaud Hermann Assouka; Massala, Eddy Guembou; Mibantsa , Guichel Souaty; Mayenga , Kester; Hell, Joseph Victor; Kankeu, Boniface; Boudzoumou, Florent (Emerging Issues in Environment, Geography and Earth Science Vol. 7, 2024)
Placer accounts for nearly 31% of global gold production between 1984 and 2006. The Elogo region has a historical legacy of artisanal and semi-industrial gold placer mining dating back to colonial times. Currently, the area is undergoing extensive exploration targeting a primary gold deposit. This study aims to contribute to understanding the primary gold deposit in the Elogo Region in the North-West of the Congo Republic. The methodological approach involved the comprehensive characterization of placer deposits, encompassing lithological and mineralogical aspects and the morphological features of gold grains. The objective was to delineate the origin of gold in relation to the local geological context. The obtained results reveal that the alluvial deposits are polygenic, comprising seventeen mineral species, namely zircon, olivine, magnetite, ilmenite, gold, garnet, rutile, coltan, cassiterite, monazite, apatite, amphibole, tourmaline, pyrite, limonite, chromite, and amphibole. Morphoscopic analysis of gold grains indicates the presence of single grains and grains with quartz inclusions, suggesting an association with quartz veins. Gold grains exhibit flattened, sub-flattened, and rounded morphologies. In the northern Elogo region, coarser quartz-included gold grains are prevalent, which implies a proximal source (within 50 meters). Conversely, the southern region displays finer and more evolved grains with choc marks, indicating a distal source (beyond 300 meters). Multivariate statistical analysis delineates seven sample classes corresponding to distinct mineralogical parageneses, pointing to varied sources, including high-grade metamorphic rocks, granitoids, pegmatites, basic and ultrabasic rocks, and banded iron formations (BIFs), which contributed minerals to the placer deposits. Gold predominantly originates from hydrothermal quartz veins, potentially undergoing peptization from the weathering of sulfides in the BIF. Therefore, in the Elogo region, exploration efforts for primary gold deposits should focus on identifying and tracing the hydrothermal system within the area. The integration of chemical analyses for both gold grains and associated minerals is imperative to enhance the precision of proposed geochemical prospecting strategies.